2008
DOI: 10.1152/ajpgi.00056.2008
|View full text |Cite
|
Sign up to set email alerts
|

Luminal regulation of normal and neoplastic human EC cell serotonin release is mediated by bile salts, amines, tastants, and olfactants

Abstract: Mechanisms by which gut luminal content regulates secretion and motility are ill understood. We evaluated whether neuroendocrine enterochromaffin (EC) cells act as luminal sensors for a wide variety of nutrients and defined the secretory mechanisms of this process. Pure (98-99%) FACS-sorted human EC cells and neoplastic EC cells (KRJ-I) were studied. RT-PCR identified transcripts for T2R1 (bitter), OR1G1 (class II olfactory) and trace amine (TAR1) G protein-coupled receptors (GPCRs) and transporters for glutam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
180
0
2

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 199 publications
(186 citation statements)
references
References 83 publications
4
180
0
2
Order By: Relevance
“…main source of serotonin, and the changes of physical conditions during digestive processes stimulate its secretion [21].…”
Section: Rycina 5 Korelacja Między Wydalaniem 6-sulfatoksymelatoninymentioning
confidence: 99%
“…main source of serotonin, and the changes of physical conditions during digestive processes stimulate its secretion [21].…”
Section: Rycina 5 Korelacja Między Wydalaniem 6-sulfatoksymelatoninymentioning
confidence: 99%
“…Beginning in 2000, ORs have been repeatedly reported also to be expressed in non-olfactory tissues (De la Cruz et al 2009;Feldmesser et al 2006;Zhang et al 2007) where they play additional roles. Some ORs govern sperm chemotaxis (Fukuda and Touhara 2006;Spehr et al 2004), inhibit prostate cancer cell proliferation (Neuhaus et al 2009), regulate cell migration and adhesion in muscle (Griffin et al 2009), and regulate serotonin secretion of gastro-intestinal cells (Braun et al 2007;Kidd et al 2008). ORs are also reported to be tumor markers (Leja et al 2009;Weng et al 2005).…”
Section: Introductionmentioning
confidence: 99%
“…[29][30][31][32][33] Another study, however, showed no difference in CCK and GLP-1 levels in duodenal tissue between the sucralose and control groups. However, there was a significant increase in both hormone levels above controls when sucralose was combined with pea protein, suggesting that there may be a synergistic relationship between a macronutrient and sucralose to enhance incretin release.…”
Section: Cellular/animal Studiesmentioning
confidence: 94%